A highly infective plasmodium vivax strain adapted to Aotus monkeys: quantitative haematological and molecular determinations useful for P. vivax malaria vaccine development (2003)
The New World primate Aotus nancymaae is susceptible to infection by the human malaria parasite Plasmodium vivax and has therefore been recommended by the World Health Organization as a model for malaria vaccine candidate evaluation. We report the isolation, adaptation, titration and genetic characterization of a P. vivax wild strain in splenectomized A. nancymaae monkeys. Parasitemia remained high after 22 passages, reaching 7.88% by Giemsa and Acridine Orange staining and Real-Time PCR determination, making this P. vivax strain a highly infective and reliable asset to be used in P. vivax biological studies and vaccine development.